Pemberdayaan kelompok pembudidaya ikan bandeng tanpa duri melalui diversifikasi produk di Kabupaten Pinrang - Mantasia Mantasia; Saliruddin Saliruddin; Hendra Jaya (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this program was to empower thecultivator group of milkfish filet through diversification ofprocessed products. This program was made according to theresults of identification problems and potential processing ofmilkfish meat in Suppa District, Pinrang Regency. Somerelated activities included: 1) Increased partner knowledge incultivating milkfish through training; 2) Increased knowledgeof milkfish farmers (partners) in processing milkfish into otherprocessed food products (diversification of processedproducts), for example, to become meatballs, nugget, andtumpi-tumpi. The results of the implementation of this activitywere: 1) The program was conducted in Tasiwalie Village,Suppa District, Pinrang Regency, South-Sulawesi. One of thefishery products that is often consumed by Tasiwalie villagersis milkfish. Milkfish is a fishery commodity that quite tastyand savory so that it is much popular in the community; 2)Long-term planning of Empowerment Activities for milkfishfilet cultivator group through product diversification isopening small business/water industry units, in this case,milkfish cultivation, management pattern, diversification ofprocessed milkfish products into other forms; and 3) Theassessment results in the implementation of Empowerment ofMilkfish Cultivator Group through Product Diversification inSuppa District, Pinrang Regency, South-Sulawesi revealedoverall mean score was 4.55 (with Good Criteria).